Racial profiling: research, racism and resistance - Glover, Karen S. (Issues in crime & justice, 2009)
Introduction: To a critical race criminology -- History, entre, and the rise of racial profiling research -- Defending the constitution? -- The racial project of mainstream criminology's approach to understanding racial profiling -- Critical race methodology and race theory -- Concepts in citizenship -- An ethnographic reading of racial profiling -- Vicarious experience, panopticonism, and oral history -- Conclusion